B Cell Development in the Bone Marrow Is Regulated by Homeostatic Feedback Exerted by Mature B Cells - Shahaf, Gitit; Zisman-Rozen, Simona; Benhamou, David; Melamed, Doron; Mehr, Ramit (Frontiers in Immunology, 2016)
Cellular homeostasis in the B cell compartment is strictly imposed to balance cell production and cell loss. However, it is not clear whether B cell development in the bone marrow (BM) is an autonomous process or subjected to regulation by the peripheral B cell compartment. To specifically address this question, we used mice transgenic for human CD20, where effective depletion of B lineage cells is obtained upon administration of mouse-anti-human CD20 antibodies, in the absence of any effect on other cell lineages and/or tissues. We followed the kinetics of B cell return to equilibrium by BrdU labeling and flow cytometry and analyzed the resulting data by mathematical modeling. Labeling was much faster in depleted mice. Compared to control mice, B cell-depleted mice exhibited a higher proliferation rate in the pro-/pre-B compartment, and higher cell death and lower differentiation in the immature B cell compartment. We validated the first result by analysis of the expression of Ki67, the nuclear protein expressed in proliferating cells, and the second using Annexin-V staining. Collectively, our results suggest that B lymphopoiesis is subjected to homeostatic feedback mechanisms imposed by mature B cells in the peripheral compartment.